2009
DOI: 10.2337/dc09-0295
|View full text |Cite
|
Sign up to set email alerts
|

Wound Chronicity, Inpatient Care, and Chronic Kidney Disease Predispose to MRSA Infection in Diabetic Foot Ulcers

Abstract: OBJECTIVETo determine the microbiological profile of diabetes-related foot infections (DRFIs) and the impact of wound duration, inpatient treatment, and chronic kidney disease (CKD).RESEARCH DESIGN AND METHODSPostdebridement microbiological samples were collected from individuals presenting with DRFIs from 1 January 2005 to 31 December 2007.RESULTSA total of 653 specimens were collected from 379 individuals with 36% identifying only one isolate. Of the total isolates, 77% were gram-positive bacteria (staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
45
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 4 publications
(2 reference statements)
11
45
0
2
Order By: Relevance
“…In our study, we observed, 21% of Staphylococcus aureus isolates were resistant to Methicillin, which is in accordance with the results of the study conducted by Yates et al, 2009. In this study, Pseudomonas aeruginosa were highly sensitive to piperacillin tazobactam (93.3%), followed by imipenem, (86.7%) and ceftazidime (66.6%), amikacin (66.6%), ciprofloxacin (66.6%). Sensitivity pattern on Pseudomonas correlated with the other studies (Bansal et al, 2008;Sekhar et al, 2014).…”
Section: S (%) S (%) S (%) S (%) ---supporting
confidence: 81%
“…In our study, we observed, 21% of Staphylococcus aureus isolates were resistant to Methicillin, which is in accordance with the results of the study conducted by Yates et al, 2009. In this study, Pseudomonas aeruginosa were highly sensitive to piperacillin tazobactam (93.3%), followed by imipenem, (86.7%) and ceftazidime (66.6%), amikacin (66.6%), ciprofloxacin (66.6%). Sensitivity pattern on Pseudomonas correlated with the other studies (Bansal et al, 2008;Sekhar et al, 2014).…”
Section: S (%) S (%) S (%) S (%) ---supporting
confidence: 81%
“…Foot infections following skin ulceration are also common causes of hospitalization for diabetic patients (6). These infectious complications seriously impair prognoses for diabetic patients (44).…”
mentioning
confidence: 99%
“…Especially, Staphylococcus aureus is a major pathogen in these infections (44). Methicillin-resistant S. aureus (MRSA) also has become prevalent among both nosocomial and community-acquired infections in diabetic patients (44).…”
mentioning
confidence: 99%
“…The elderly had been reported to have worse prognosis when infected due to immobility, poor nutrition and prior exposure to antibiotics [21,22] . Studies have also shown that patients with these underlying diseases were prone to MRSA infections [23][24][25] . Diabetic patients possess higher risk because it is likely for them to develop complications, such as foot ulcers, that predispose them to infections [26] .…”
Section: Discussionmentioning
confidence: 99%